SENACA FL-09: a new improved rice variety for Ecuador - CGIAR Research Program on Rice (2019)
Rice variety with improved yield widely used in irrigated rice producing systems in Ecuador. Rice variety with improved yield widely used in irrigated rice producing systems in Ecuador. The variety has been used by 3,851 farmers between 2014 and 2019.